Lower ventricular and atrial strain in patients who recovered from COVID-19 assessed by cardiovascular magnetic resonance feature tracking - Mojica-Pisciotti, Mary Luz; Panovský, Roman; Holeček, Tomáš; Opatřil, Lukáš; Feitová, Věra (Frontiers in Cardiovascular Medicine, 2023)
Introduction One of the most common complications of coronavirus disease 2019 (COVID-19) is myocardial injury, and although its cause is unclear, it can alter the heart's contractility. This study aimed to characterize the ventricular and atrial strain in patients who recovered from COVID-19 using cardiovascular magnetic resonance feature-tracking (CMR-FT). Methods In this single-center study, we assessed left ventricle (LV) and right ventricular (RV) global circumferential strain (GCS), global longitudinal strain (GLS), global radial strain (GRS), left atrial (LA) and right atrial (RA) longitudinal strain (LS) parameters by CMR-FT. The student's t-test and Wilcoxon rank-sum test were used to compare the variables. Results We compared seventy-two patients who recovered from COVID-19 (49 ± 16 years) to fifty-four controls (49 ± 12 years, p = 0.752). The patients received a CMR examination 48 (34 to 165) days after the COVID-19 diagnosis. 28% had LGE. Both groups had normal LV systolic function. Strain parameters were significantly lower in the COVID-19 survivors than in controls. Discussion Patients who recovered from COVID-19 exhibited significantly lower strain in the left ventricle (through LVGCS, LVGLS, LVGRS), right ventricle (through RVGLS and RVGRS), left atrium (through LALS), and right atrium (through RALS) than controls.